Understanding perseverance and persistence in relation to students’ mathematical wellbeing - Hill, Julia; Hunter, Jodie (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
Student mathematical wellbeing (MWB) declines as students progress through school. This study investigates the role of perseverance and persistence in supporting students' MWB, focusing on how these qualities manifest in the context of mathematical learning. Based on a survey with 13,381 students across Grades Three to Ten in New Zealand, our findings revealed a decline in students' experiences of perseverance and persistence across grade levels, particularly during transitional periods. Qualitative analysis of student responses highlighted the relationship between perseverance, persistence, and MWB. Students who reflected on perseverance as an enabler of their MWB often associated it with overcoming mathematical challenges, which provided a sense of accomplishment and positive emotions upon successful task completion. The study underscores the importance of fostering perseverance and persistence within a supportive classroom environment to enhance students' mathematical understanding and overall MWB. Our findings contribute to the growing body of research on mathematical affect and provide insights into how educators can cultivate perseverance and persistence to create more positive and engaging mathematical learning experiences to support the MWB for all students.